Selective deintercalation of apex over face-shared oxide ions in the topotactic reduction of Sr7Mn4O15 to Sr7Mn4O12. - Hayward, M (2004)
Sodium hydride selectively deintercalates the apex rather than face-shared oxide ions within the structure of Sr(7)Mn(4)O(15) leading to the formation of the structurally related reduced phase Sr(7)Mn(4)O(12).